Exploring the Transesterification of Castor Oil to Produce Second Generation Biodiesel using a Novel Catalyst - Mardhiana, Ismail; Ghazi Faisal, Najmuldeen; Wan Mohd Hafizuddin, Wan Yussof (ESRSA Publications Pvt. Ltd., 2015)
In this study, the crude oil of Malaysian castor bean Ricinus cummunis L. which is non-edible oil was extracted by microwave-assisted extraction (MAE) using ethanol and follow by transesterification reaction by using heterogeneous activated cement clinker catalyst (ACCC). MAE procedure takes 15-30 min and uses small solvent volumes (50% of weight oil). The biodiesel yield when using 1% was 88.61 % which is highest compare with catalyst loading 0.5%,0.75%,1.25% and 1.5 wt/wt%. Reaction time affected positively the catalytic activity since the conversion percentage increased steadily with the reaction time with 2 hours is the best reaction time give yield percentage is 93.91%. Experiment works were carried out varying oil to methanol ratio 1:3, 1:6 and and 1:9 keeping other parameter constant, reaction temperature, 60 °C and reaction time in 2 hour. It show that, best oil to methanol ratio was 1:6 with give biodiesel yield 96.90%.